The Antimicrobial Peptide MPX Can Kill Staphylococcus aureus, Reduce Biofilm Formation, and Effectively Treat Bacterial Skin Infections in Mice - Zhu, Chunling; Zhao, Yaya; Zhao, Xueqin; Liu, Shanqin; Xia, Xiaojing; Zhang, Shouping; Wang, Yimin; Zhang, Huihui; Xu, Yanzhao; Chen, Shijun; Jiang, Jinqing; Wu, Yundi; et al. (Frontiers in Veterinary Science, 2022)
Staphylococcus aureus is a common pathogen that can cause pneumonia and a variety of skin diseases. Skin injuries have a high risk of colonization by S. aureus, which increases morbidity and mortality. Due to the emergence of multidrug-resistant strains, antimicrobial peptides are considered to be among the best alternatives to antibiotics due to their unique mechanism of action and other characteristics. MPX is an antibacterial peptide extracted from wasp venom that has antibacterial activity against a variety of bacteria. This study revealed that MPX has good bactericidal activity against S. aureus and that its minimum inhibitory concentration (MIC) is 0.016 µM. MPX (4 MIC) can kill 99.9% of bacteria within 1 h, and MPX has good stability. The research on the bactericidal mechanism found that MPX could destroy the membrane integrity, increase the membrane permeability, change the membrane electromotive force, and cause cellular content leakage, resulting in bactericidal activity. Results from a mouse scratch model experiment results show that MPX can inhibit colonization by S. aureus, which reduces the wound size, decreases inflammation, and promotes wound healing. This study reports the activity of MPX against S. aureus and its mechanism and reveals the ability of MPX to treat S. aureus infection in mice, laying the foundation for the development of new drugs for bacterial infections.